2019
DOI: 10.1186/s40663-019-0194-y
|View full text |Cite
|
Sign up to set email alerts
|

Litterfall dynamics along a successional gradient in a Brazilian tropical dry forest

Abstract: Background: This study aimed to determine the influence of soil traits, vegetation structure and climate on litterfall dynamics along a successional gradient in a tropical dry forest (TDF) in southeastern Brazil. We used a chronosequence design consisting of three successional stages (early, intermediate, and old-growth) defined based on forest age and vertical and horizontal structures. Methods: Litterfall was recorded monthly for three years in 12 plots of 50 × 20 m (four plots per stage) where vegetation pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 50 publications
(83 reference statements)
6
32
0
1
Order By: Relevance
“…3b), several studies have also reported the The mean values followed by the same letters (lowercase among the three areas in the same season and uppercase in each area between the two seasons) did not differ statistically by the Tukey Test (p < 0.05). AD = Agua Doce palm swamp; CV = Capivara palm swamp; BG = Buriti Grosso palm swamp maximum litter production in the dry period (Klinge and Rodrigues 1968;Luizão and Schubart 1987;Boinskis 1989;Martins 2010;Brasil et al 2017;Souza et al 2019). The leaf deciduousness of the Cerrado species in the dry season constitutes a plant protection mechanism to minimize the effects of water shortage, increases the litter deposition in the months with low rainfall (Souza et al 2019) and reduces loss of water through evapotranspiration and thereby maintains plant metabolism (Herbohn and Congdon 1993;Franco et al 2005), We observed that, even considering the distinct anthropization processes of the three ecosystems evaluated, there is a seasonal pattern of litterfall deposition in the Cerrado surrounding the palm swamps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3b), several studies have also reported the The mean values followed by the same letters (lowercase among the three areas in the same season and uppercase in each area between the two seasons) did not differ statistically by the Tukey Test (p < 0.05). AD = Agua Doce palm swamp; CV = Capivara palm swamp; BG = Buriti Grosso palm swamp maximum litter production in the dry period (Klinge and Rodrigues 1968;Luizão and Schubart 1987;Boinskis 1989;Martins 2010;Brasil et al 2017;Souza et al 2019). The leaf deciduousness of the Cerrado species in the dry season constitutes a plant protection mechanism to minimize the effects of water shortage, increases the litter deposition in the months with low rainfall (Souza et al 2019) and reduces loss of water through evapotranspiration and thereby maintains plant metabolism (Herbohn and Congdon 1993;Franco et al 2005), We observed that, even considering the distinct anthropization processes of the three ecosystems evaluated, there is a seasonal pattern of litterfall deposition in the Cerrado surrounding the palm swamps.…”
Section: Discussionmentioning
confidence: 99%
“…In natural ecosystems of palm swamps, most of the organic matter accumulated on the soil surface mainly consists of plant matter coming from the litterfall decomposition process, which is highly relevant to the nutrient cycling (Souza et al 2019). The decomposition process results in accumulation of soil organic matter (SOM) and release of its nutrients (Sousa Neto et al 2017), maintaining the soil fertility and ecosystem productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The sandy textures of Mussununga soils apparently also influenced the higher contribution of leaves to total litterfall in relation to the Mata Alta forest. Soils with higher sand content and lower clay content retain less water (Pastor & Post, 1986) and allow increased litter deposition from plants (Souza et al, 2019). Thus, the arboreal community in the Mussununga phytophysiognomy likely demonstrates higher leaf abscission than the Mata Alta area to reduce water loss through evapotranspiration.…”
Section: Fine Litterfallmentioning
confidence: 99%
“…Tropical forests are characterized by a strong seasonality in their leaf litterfall pattern (Zhang et al 2014;Becker et al 2015;Wagner et al 2016;Nakagawa et al 2019), and the seasonality depends on the vegetation characteristics, species composition and plant phenological responses to environmental variation (Cuevas and Lugo 1998;Zalamea and Gonzalez 2008;Schilling et al 2016;Souza et al 2019). In tropical dry forests leaf loss mostly occurs during the dry season (Barlow et al 2007;Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%